Frequency and clinical correlates of elevated plasma Epstein‐Barr virus DNA at diagnosis in peripheral T‐cell lymphomas. Issue 8 (15th April 2017) - Haverkos, Bradley M.; Huang, Ying; Gru, Alejandro; Pancholi, Preeti; Freud, Aharon G.; Mishra, Anjali; Ruppert, Amy S.; Baiocchi, Robert A.; Porcu, Pierluigi
Abstract : Epstein‐Barr virus (EBV)‐encoded RNAs (EBER) in tumor tissue and cell‐free plasma EBV‐DNA (pEBVd) are detected in EBV‐associated lymphomas. Studies have suggested that EBER+ peripheral T‐cell lymphomas (PTCL) have worse prognosis but the role of EBV in these neoplasms remains unclear. pEBVd is quantitative and more easily amenable to standardization than EBER, but frequency of pEBVd detection, clinical impact and agreement with EBER status in PTCL are unknown. We retrospectively assessed frequency of detectable pre‐treatment pEBVd, presence of EBER in tumor tissue, and outcomes in 61 of 135 EBV‐assessable PTCL patients. Fifteen of 61 patients (24.5%, 95% CI: 14–37%) were pre‐treatment pEBVd+, with no significant differences in baseline characteristics or treatment between pEBVd+ and pEBVd− patients. EBER‐ISH was performed on 10 pEBVd+ and 35 pEBVd− tumors. All 10 pEBVd+ patients were EBER+, but 9 pEBVd− patients were also EBER+. With median follow up of 24 months (range 1–96), overall survival (OS) was shorter in pEBVd+ compared to pEBVd− patients (13 vs . 72 months; p = 0.04). In our retrospective study, pre‐treatment pEBVd was elevated in 25% of PTCL patients, was highly specific for EBER+ tumors, and was associated with shorter survival. pEBVd should be further explored as a prognostic variable and tumor biomarker in PTCL. Abstract : What's new? The association of Epstein‐Barr virus (EBV) with peripheral T‐cell lymphoma (PTCL) suggests that EBV may be prognostically relevant for the disease. Little is known, however, about the frequency with which plasma EBV‐DNA (pEBVd) occurs in PTCL, whether pEBVd is clinically significant, and whether pEBVd detection agrees with EBV‐encoded RNA (EBER) status. In this retrospective study, pEBVd was detected in 25% of PTCL patients and was found to be highly specific for EBER‐positive tumors. Furthermore, the presence of pEBVd was associated with poor survival. These findings support additional investigation of pEBVd as a prognostic and predictive biomarker in PTCL.